1981
DOI: 10.1104/pp.67.5.898
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation and Vegetative Regrowth of Alfalfa and Birdsfoot Trefoil after Successive Harvests or Floral Debudding

Abstract: Nitrogenase-dependent acetylene reduction, leaf, herbage, and root growth, and total nonstructural carbohydrate accumulation of alfalfa (Medicago sativa L.) and birdsfoot trefoil (Lotus corniculatus L.) were compared to learn how nitrogen fixation capacity and vegetative growth respond to partial (75-85%) or total shoot and leaf removal, and floral debudding. Treatments were imposed on greenhouse-grown plants during two successive harvest cycles.Both species displayed an initial decline in total nitrogenase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
1
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 17 publications
3
21
1
1
Order By: Relevance
“…The second harvest, however, may have led to the loss of other forms ofN. Cralle and Heichel (1979) and Vance et al (1979) reported temporary senescence of root and nodule tissue of alfalfa after herbage removal. Such senescence could have contributed to increased N loss after both the first and second harvests (Fig.…”
Section: Relationship To Other Researchmentioning
confidence: 95%
“…The second harvest, however, may have led to the loss of other forms ofN. Cralle and Heichel (1979) and Vance et al (1979) reported temporary senescence of root and nodule tissue of alfalfa after herbage removal. Such senescence could have contributed to increased N loss after both the first and second harvests (Fig.…”
Section: Relationship To Other Researchmentioning
confidence: 95%
“…The persistence of forage legumes may depend in part on the sensitivity of N2 fixation to defoliation (1). It was previously assumed that the principal effect of defoliation on N2 fixation was a reduction in photosynthate supply.…”
mentioning
confidence: 99%
“…N2 fixation is reportedly more sensitive to defoliation in birdsfoot trefoil than in alfalfa, possibly because ofgreater nonstructural carbohydrate reserves in alfalfa (1). We also used nodule respiration data to test the hypothesis that nodule permeability changes are triggered by decreased availability of carbon substrates for respiration.…”
mentioning
confidence: 99%
“…This result could be closely related to lowered activities of enzymes such as nitrate reductase or nitrogenase (Cralle and Heichel, 1981;Macdowall 1983;Vance and Heichel, 1981), and to the decline in photosynthesis and carbohydrate reserves (Davidson et al, 1990;Gonzalez et al, 1989;Hodgkinson, 1969;Smith and Silva, 1969) after defoliation. On the other hand, shoot removal induced higher levels of N outflow from N reserves of roots and remaining parts of shoots (both acting as source organs).…”
Section: Discussionmentioning
confidence: 99%